ADP-ribosylation factor-like 8b is required for the development of mouse models of systemic lupus erythematosus. (7th February 2019) - Saitoh, Shin-Ichiroh; Saitoh, Yoshiko Mori; Kontani, Kenji; Sato, Katsuaki; Miyake, Kensuke
Abstract: Toll-like receptor 7 (TLR7) and type I interferons (IFN-1) are essential for the development of systemic lupus erythematosus (SLE) models such as BXSB. Yaa and 2, 6, 10, 14-tetramethyl-pentadecane (TMPD)-induced experimental lupus. However, the mechanism underlying the development of SLE remains undefined. We report a requirement for ADP-ribosylation factor-like 8b (Arl8b) for TLR7-dependent IFN-1 production in plasmacytoid dendritic cells (pDCs). We analyzed whether Arl8b plays a role in two SLE models by comparing wild-type and Arl8b-deficient Arl8b GeneTrap ( Arl8b Gt/Gt ) mice. We found that BXSB. Yaa Arl8b Gt/Gt mice showed none of the abnormalities characterized in BXSB. Yaa mice. TMPD treatment of Arl8b Gt/Gt mice significantly inhibited the development of SLE. pDCs were required for TMPD-induced peritonitis. Our data demonstrate that Arl8b contributes to disease pathogenesis in two SLE models via IFN-1-dependent and -independent mechanisms and suggest that Arl8b is an attractive new target for therapeutic intervention in SLE. Abstract : Arl8b is essential for SLE development